The globalising world of DIY house improvement: interpreting a cultural and commercial phenomenon. Issue 6 (18th August 2017) - Mackay, Michael; Perkins, Harvey C.
Abstract: This paper reports a study of DIY house improvement focusing on its globalising material and commercial elements. Using a multi-method approach and a New Zealand case study we illustrate the importance in housing studies, and research into homemaking in particular, of taking account of DIY practice. We emphasise that it is not possible for housing researchers to account fully for the role and function of DIY without interpreting it as a cultural and economic phenomenon. The ways people live in and make their houses demands a focus on DIY practices, identity, homeownership, government regulation and the globalising commercial features of DIY which include: international product manufacturing, big-box retailing, tool and materials distribution and advertising, the production of printed and digital instructional material, and new popular media forms, such as DIY reality television. DIY is thus an excellent example of culture and economy combined.